Policy On The Formulation of Criminal Law On Illegal Firearm Ownership In Criminal Law Reform In Indonesia - Mundzir Rasyid, Abal; Safiranata, Arisandy; Athur, Mohamad; Rahman, Alip; Dimyati, Agus (Devotion : Journal of Research and Community Service, 2025)
Firearm abuse is the most frequent case today. A firearm for the general public is an object/tool used to attack or defend oneself which as a result if shot by a firearm can cause serious injury or death and one of the most disturbing crimes for the community is the crime of using firearms. The flow of crime using the threat of violence and with firearms is indeed very disruptive to public security and order, causing concern in the community.